Número y variación estacional de asociaciones hormiga-planta en un bosque montano bajo de Veracruz, México. - Díaz Castelazo, Cecilia; Rico Gray, Víctor (Instituto de Ecología, A.C., 1998)
We quantified the number and seasonal variation of ant-plant associations mediated by néctar and homopteran honeydew in a low montane forest near Xalapa, Veracruz, México. We registered five ant specíes and 12 specias of angiosperms in 17 associations; we did not find obligate associations. Ant species differentially used the avaílable food resources: they used extrafloral néctar more, and floral néctar and honeydew less. The generalizad linear modal adjusted to the ant-plant associations curve explained 29% of the total variation. Precipitation alone explained 14%, and the interaction between factors (precipitation-temperature) explained 15% of the variation. Our results indicate that: (1) a low proportion of plants assocíated with anta in the low montane forest studied; (2) the environmental factors considered do not explatn the seasonal variation and the number of ant-plant associations; and (3) the low number of ant-plant associations is probably due to the low percentage of plant species bearing extrafloral nectaries, this beíng the result of an abundance of Holarctic or températe elements.